Electrode including active material layer having double-layer structure, method for manufacturing the same, and secondary battery including the same
Patent Information
- Application Number
- CN202180065515.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-03
- Filing Date
- 2021-11-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-11-03
AI Technical Summary
然而,当以单层电极的形式形成此类高负载电极时,电极浆料中所含的粘合剂不能均匀地分散在电极活性材料层中,并且可容易浮在电极活性材料层的表面上
[0025]根据本发明,通过在与集流体接触的最下部和与隔膜接触的最上部使用不同组成的粘合剂,可以提高多层结构化电极的结合力和电阻特性。当使用通过控制最上部和最下部的粘合剂组成以具有合适的成分组成而获得的多层结构化电极时,可以进一步提高电池性能,包括容量、寿命或输出等。
Smart Images

Figure BDA0004142993130000051 
Figure BDA0004142993130000061 
Figure BDA0004142993130000062
Abstract
Description
Technical Field
[0001] This application claims priority to Korean Patent Application No. 10-2020-0145516, filed in Korea on November 3, 2020. The present invention relates to an electrode for an electrochemical device. Specifically, the present invention relates to an electrode for an electrochemical device that exhibits improved adhesion to a current collector not only in a dry state before contact with an electrolyte but also in a wet state after being wetted by the electrolyte. The present invention also relates to an electrochemical device including this electrode. Background Technology
[0002] With technological advancements and increasing demand for mobile devices, there is a growing need for rechargeable, miniaturized, and high-capacity secondary batteries. Furthermore, among these secondary batteries, lithium-ion batteries with high energy density and operating voltage have been commercialized and are widely used.
[0003] A lithium secondary battery has a structure comprising an electrode assembly (each having a positive electrode and a negative electrode, each comprising an active material coated on an electrode current collector, and a porous membrane disposed between the two electrodes); and an electrolyte containing a lithium salt injected into the electrode assembly. The electrode is obtained by coating a slurry comprising an active material, a binder, and a conductive material dispersed in a solvent onto a current collector, followed by drying and pressing.
[0004] Meanwhile, with the increasing demand for secondary batteries in electric vehicles and energy storage systems in recent years, electrodes with high-load electrode active materials are needed to provide batteries with high capacity and high energy density. However, when such high-load electrodes are formed in the form of a monolayer electrode, the binder contained in the electrode slurry cannot be uniformly dispersed in the electrode active material layer and can easily float on the surface of the electrode active material layer. In this case, the battery resistance increases due to the binder, leading to a decrease in battery performance. Summary of the Invention
[0005] [Technical Issues]
[0006] This invention is designed to solve the problems of related technologies; therefore, it aims to provide an electrode comprising a multilayer structured electrode active material layer, allowing a binder material to be uniformly dispersed within the electrode. This invention also aims to provide an electrode that exhibits improved peel strength between the electrode active material layer and the current collector and improved resistive characteristics by using a binder resin of different compositions in each electrode active material layer.
[0007] [Technical Solution]
[0008] According to a first embodiment of the present invention, an electrode for an electrochemical device is provided, comprising: an electrode current collector; and a multilayer structured electrode active material layer disposed on at least one surface of the electrode current collector and having two or more stacked sublayers.
[0009] The electrode active material layer comprises an electrode active material, a binder resin, and a conductive material.
[0010] The bottom layer of the multilayer structured electrode active material layer includes a copolymer resin (A) as a binder resin, and the top layer is disposed above the bottom layer. Furthermore, the top layer of the multilayer structured electrode active material layer includes a copolymer resin (B) as a binder resin.
[0011] The copolymer resin (A) is a copolymer containing at least one repeating unit selected from (a) a vinyl aromatic monomer; (b) a conjugated dienyl monomer; (c) a repeating unit derived from a vinyl cyanide compound; and (d) a repeating unit derived from a (meth)acrylate compound.
[0012] The copolymer resin (B) is a copolymer containing at least one selected from (a) a vinyl aromatic monomer; (b) a conjugated dienyl monomer; (c) a repeating unit derived from a vinyl cyanide compound; and (d) a repeating unit derived from a (meth)acrylate compound.
[0013] The sum of the contents (by weight) of repeating unit (c) and repeating unit (d) in the adhesive resin of the uppermost layer is greater than the sum of the contents (by weight) of repeating unit (c) and repeating unit (d) in the adhesive resin of the lowermost layer.
[0014] According to a second embodiment of the present invention, an electrode for an electrochemical device as defined in the first embodiment is provided, wherein the vinyl cyanide compound is at least one selected from acrylonitrile and methacrylonitrile.
[0015] According to a third embodiment of the present invention, an electrode for an electrochemical device as defined in the first or second embodiment is provided, wherein the (meth)acrylate compound is at least one selected from methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, and 2-ethylhexyl methacrylate.
[0016] According to a fourth embodiment of the present invention, an electrode for an electrochemical device as defined in any one of the first to third embodiments is provided, wherein the lowest layer comprises a copolymer resin (A) containing at least two of the following: (a) a vinyl aromatic monomer; (b) a conjugated diene monomer; (c) a repeating unit derived from a vinyl cyanide compound; and (d) a repeating unit derived from a (meth)acrylate compound as an adhesive resin.
[0017] According to a fifth embodiment of the present invention, an electrode for an electrochemical device as defined in any one of the first to fourth embodiments is provided, wherein the uppermost layer comprises a copolymer resin (B) containing at least three of the following: (a) a vinyl aromatic monomer; (b) a conjugated diene monomer; (c) a repeating unit derived from a vinyl cyanide compound; and (d) a repeating unit derived from a (meth)acrylate compound as an adhesive resin.
[0018] According to a sixth embodiment of the present invention, an electrode for an electrochemical device as defined in any one of the first to fifth embodiments is provided, wherein the bottom layer comprises a quaternary copolymer of styrene-butadiene-acrylonitrile-repeating unit (d) and / or a binary copolymer of styrene-butadiene as an adhesive resin, and the repeating unit (d) is derived from butyl acrylate and / or methyl methacrylate.
[0019] According to a seventh embodiment of the present invention, an electrode for an electrochemical device as defined in the sixth embodiment is provided, wherein the styrene-butadiene-acrylonitrile-repeating unit (d) quaternary copolymer comprises acrylonitrile repeating units and repeating units (d) comprising 20% or less of 100% by weight of the quaternary copolymer.
[0020] According to an eighth embodiment of the present invention, an electrode for an electrochemical device as defined in any one of the first to seventh embodiments is provided, wherein the lowest layer comprises a quaternary copolymer of styrene-butadiene-acrylonitrile-repeating unit (d) as an adhesive resin, and the repeating unit (d) is derived from butyl acrylate and / or methyl methacrylate.
[0021] According to a ninth embodiment of the present invention, an electrode for an electrochemical device as defined in any one of the first to eighth embodiments is provided, wherein the content (by weight) of the bottommost conductive material in 100% of the bottommost layer is equal to or higher than the content (by weight) of the topmost layer in 100% of the conductive material.
[0022] According to a tenth embodiment of the present invention, an electrode for an electrochemical device as defined in any one of the first to ninth embodiments is provided, which is a negative electrode.
[0023] According to the eleventh embodiment of the present invention, a lithium-ion secondary battery is provided, which includes an electrode for an electrochemical device as defined in any one of the first to tenth embodiments.
[0024] [Beneficial Effects]
[0025] According to the present invention, by using adhesives of different compositions at the bottommost part in contact with the current collector and at the topmost part in contact with the separator, the bonding strength and resistivity characteristics of the multilayer structured electrode can be improved. When using a multilayer structured electrode obtained by controlling the composition of the adhesives at the top and bottommost parts to have a suitable composition, battery performance, including capacity, lifespan, or output, can be further improved. Detailed Implementation
[0026] Preferred embodiments of the invention will be described in detail below. Before the description, it should be understood that the terminology used in the specification and appended claims should not be construed as limited to its general or dictionary meaning, but rather should be interpreted based on the meaning and concept corresponding to the technical aspects of the invention, in accordance with the principle that the inventors are allowed to appropriately define the terminology for the best interpretation.
[0027] Throughout the specification, the statement "a section includes one element" does not exclude the existence of any other elements, but rather means that the section may further include other elements.
[0028] As used herein, the terms “approximately” or “substantially” are used to indicate a continuation from the stated numerical value to both sides, where acceptable errors in preparation and materials are indicated for the purposes of preventing unethical infringers from misusing the disclosure containing accurate or absolute numerical values. Providing accurate or absolute numerical values is to aid in understanding the invention.
[0029] As used in this article, the expression "A and / or B" means "A, B, or both of them".
[0030] The specific terms used in the following description are for illustrative purposes and not for limitation. Terms such as “right,” “left,” “upper surface,” and “lower surface” indicate orientation in the accompanying drawings to which they are referenced. Terms such as “inward” and “outward” indicate orientation toward and away from the geometric center of the corresponding device, system, and its components, respectively. “Front,” “back,” “up,” and “down,” as well as related words and expressions, indicate position and orientation in the accompanying drawings to which they are referenced, but should not be limiting. Such terms include the words listed above, their derivatives, and words with similar meanings.
[0031] As used in this article, the symbol “*” in a chemical formula indicates that it can be combined with any other element or repeating unit.
[0032] This invention relates to electrodes for electrochemical devices and electrochemical devices including the same.
[0033] According to the present invention, the electrode comprises: an electrode current collector; and an electrode active material layer disposed on at least one surface of the electrode current collector, wherein the electrode active material layer comprises an electrode active material, an adhesive resin, and a conductive material.
[0034] According to the present invention, the electrode active material layer has a multilayer structure, including two or more stacked sublayers, particularly a bottom layer that is in contact with the current collector, and other sublayers besides the bottom layer. According to one embodiment of the present invention, the sublayer in contact with the separator is called the top layer. According to one embodiment of the present invention, the electrode active material layer may include a bottom layer and a top layer disposed above the bottom layer. According to one embodiment of the present invention, the electrode may have a bilayer structure including a bottom layer and a top layer. When the electrode has such a bilayer structure, the thickness ratio of the top layer to the bottom layer may be from 6:4 to 4:6.
[0035] The lowest layer includes a first adhesive resin, and the first adhesive resin includes a copolymer resin (A) containing at least two of the following: (a) a vinyl aromatic monomer; (b) a conjugated diene monomer; (c) a repeating unit derived from a vinyl cyanide compound; and (d) a repeating unit derived from a (meth)acrylate compound. The copolymer resin (A) may include at least one of the following: a copolymer resin (A1) containing all of the repeating units (a) to (d); a copolymer resin (A2) containing repeating units (a), (b) and (c); a copolymer resin (A3) containing repeating units (a), (b) and (d); and a copolymer resin (A4) containing repeating units (a) and (b).
[0036] Based on 100% by weight of the first adhesive resin, the amount of copolymer resin (A) may be 80% by weight or more, preferably 90% by weight or more. For example, the first adhesive resin may consist only of copolymer resin (A).
[0037] Additionally, the uppermost layer includes a second adhesive resin, and the second adhesive resin includes a copolymer resin (B) containing at least three of the following: (a) a vinyl aromatic monomer; (b) a conjugated diene monomer; (c) a repeating unit derived from a vinyl cyanide compound; and (d) a repeating unit derived from a (meth)acrylate compound. According to one embodiment of the invention, the copolymer resin (B) may include at least one of the following: a copolymer resin (B1) containing all of the repeating units (a) to (d); a copolymer resin (B2) containing repeating units (a), (b), and (c); and a copolymer resin (B3) containing repeating units (a), (b), and (d).
[0038] Based on 100% by weight of the second adhesive resin, the amount of copolymer resin (B) may be 80% by weight or more, preferably 90% by weight or more. For example, the second adhesive resin may consist only of copolymer resin (B).
[0039] Specific examples of the vinyl aromatic monomer (a) may include at least one selected from styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 1-vinylnaphthalene, 4-cyclohexylstyrene, 4-(p-methylphenyl)styrene, and 1-vinyl-5-hexylnaphthalene. According to one embodiment, the vinyl aromatic monomer (a) may include styrene and / or α-methylstyrene.
[0040] According to one embodiment of the present invention, the vinyl aromatic monomer may include at least one of the compounds represented by the following chemical formula 1:
[0041] [Chemical Formula 1]
[0042]
[0043] In this embodiment, R1 and R2 can each independently represent H or a C1-C30 straight-chain or branched alkyl group. According to one embodiment of the invention, at least one hydrogen atom of the alkyl group can be substituted with a halogen element. According to one embodiment of the invention, R1 and R2 can each independently represent methyl, ethyl, propyl, isopropyl, butyl, isobutyl, or pentyl, but are not limited thereto. In particular, R1 and R2 can each be hydrogen. In one variant, at least one of R1 and R2 can be an alkyl group. Meanwhile, in Formula 1, n is an integer greater than or equal to 1.
[0044] Specific examples of conjugated dienyl monomers (b) may include at least one selected from 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, pentadiene, 3-butyl-1,3-octadiene, isoprene and 2-phenyl-1,3-butadiene.
[0045] According to one embodiment of the present invention, the conjugated diene monomer may include at least one of the compounds represented by the following chemical formula 2:
[0046] [Chemical Formula 2]
[0047]
[0048] In this embodiment, R1, R2, R3, and R4 can each independently represent H or a C1-C30 straight-chain or branched alkyl group. According to one embodiment of the invention, at least one hydrogen atom of the alkyl group can be substituted with a halogen element. According to one embodiment of the invention, R1, R2, R3, and R4 can each independently represent methyl, ethyl, propyl, isopropyl, butyl, isobutyl, or pentyl, but are not limited thereto. In particular, R1, R2, R3, and R4 can each be hydrogen. In one variant, at least one of them can be an alkyl group, and the others can represent H. Meanwhile, in Formula 2, y is an integer greater than or equal to 1.
[0049] The repeating unit (c) derived from a vinyl cyanide compound may be a repeating unit derived from at least one selected from the group consisting of acrylonitrile, methacrylonitrile and its derivatives, particularly a repeating unit derived from acrylonitrile.
[0050] According to one embodiment of the present invention, the repeating unit (c) derived from a vinyl cyanide compound may include at least one of the repeating units represented by the following chemical formula 3:
[0051] [Chemical Formula 3]
[0052]
[0053] In this embodiment, R1 and R2 can each independently represent H or a C1-C30 straight-chain or branched alkyl group. According to one embodiment of the invention, at least one hydrogen atom of the alkyl group can be substituted with a halogen element. According to one embodiment of the invention, R1 and R2 can each independently represent methyl, ethyl, propyl, isopropyl, butyl, isobutyl, or pentyl, but are not limited thereto. In particular, at least one of R1 and R2 can be an alkyl group, and the other can represent H. Meanwhile, in Formula 3, n is an integer greater than or equal to 1.
[0054] The term (meth)acrylate includes both acrylates and methacrylates. According to one embodiment of the invention, the repeating unit (d) derived from a (meth)acrylate compound may be at least one selected from the group consisting of repeating units derived from alkyl acrylates and repeating units derived from alkyl methacrylates. Specific examples of alkyl acrylates may include at least one selected from the group consisting of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, and 2-ethylhexyl acrylate, particularly at least one selected from butyl acrylate and methyl acrylate. Additionally, specific examples of alkyl methacrylates may include at least one selected from the group consisting of methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, and 2-ethylhexyl methacrylate, particularly at least one selected from butyl methacrylate and methyl methacrylate.
[0055] According to one embodiment of the present invention, the repeating unit (d) derived from the (meth)acrylate compound may include at least one of the repeating units represented by the following chemical formula 4:
[0056] [Chemical Formula 4]
[0057]
[0058] Where A represents -(CH2). n -(where n is a number from 1 to 10), and R1, R2, and R3 can each independently represent H or a C1-C30 straight-chain or branched alkyl group. According to one embodiment of the invention, at least one hydrogen atom of the alkyl group can be substituted with a halogen element. According to one embodiment of the invention, R1, R2, and R3 can each independently represent methyl, ethyl, propyl, isopropyl, butyl, isobutyl, or pentyl, but are not limited thereto. In particular, R1, R2, and R3 can each be hydrogen. In one variant, at least one of them can be an alkyl group, and the others can represent H. Meanwhile, in Formula 4, x is an integer greater than or equal to 1.
[0059] According to one embodiment of the invention, the copolymer resin (A1) may include all of (a) to (d), wherein (c) may be a repeating unit derived from acrylonitrile, and (d) may be a repeating unit derived from butyl acrylate and methyl methacrylate.
[0060] Furthermore, based on 100% by weight of the copolymer resin (A1), the sum of the contents of (c) (by weight%) and (d) (by weight%) can be 20% by weight or less, preferably 19% by weight or less. Moreover, preferably, the sum of the contents of (c) (by weight%) and (d) (by weight%) in the lowest layer can be 20% by weight or less.
[0061] As used herein, the content of each repeating unit refers to the amount (wt%) of each repeating unit contained in each adhesive resin and / or each copolymer resin, and can be determined by... 1 Measurement by H NMR spectroscopy.
[0062] According to one embodiment of the invention, the copolymer resin (A1) may comprise a quaternary copolymer of styrene-butadiene-acrylonitrile-repeating unit (d), wherein the repeating unit (d) may comprise at least one repeating unit derived from butyl acrylate and methyl methacrylate. Additionally, the copolymer resin (A4) may comprise styrene-butadiene rubber (SBR).
[0063] According to one embodiment of the invention, the copolymer resin (B1) may comprise all of (a) to (d), wherein (c) may comprise repeating units derived from acrylonitrile, and (d) may comprise repeating units derived from butyl acrylate and methyl methacrylate. According to another embodiment of the invention, the copolymer resin (B1) may comprise a quaternary copolymer of styrene-butadiene-acrylonitrile-repeating unit (d), wherein the repeating unit (d) may comprise at least one repeating unit derived from butyl acrylate and methyl methacrylate.
[0064] According to one embodiment of the invention, the sum of the content (by weight%) of repeating units (c) and (by weight%) of repeating units (d) in the uppermost layer is preferably greater than the sum of the content (by weight%) of repeating units (c) and (by weight%) of repeating units (d) in the lowermost layer. As described above, when the total content of repeating units (c) and (d) in the lowermost layer facing the current collector is relatively low compared to the uppermost layer, the dry adhesion and wet adhesion between the electrode active material layer and the current collector remain at a high level or are improved, thus maintaining electrical contact between the electrode current collector and the electrode active material layer, thereby providing a battery with improved resistance and life characteristics.
[0065] Furthermore, according to one embodiment of the present invention, regarding the repeating units (c) and (d) in each electrode active material layer, the first adhesive resin in the bottommost layer does not include repeating units (c) and (d), or the ratio E (the sum of the content (by weight) of repeating units (c) and (d) in the topmost layer to the total content of these repeating units in the bottommost layer) is greater than 1. According to one embodiment of the present invention, E can be 1.5 or more, or 2 or more.
[0066] According to the present invention, "dry adhesion force" refers to the adhesion force between the electrode current collector and the electrode active material layer in the state after the electrode is manufactured and has not been in contact with the electrolyte, and "wet adhesion force" refers to the adhesion force between the electrode current collector and the electrode active material layer in the state after the electrode has been in contact with the electrolyte. The statement "electrode in contact with electrolyte" means that the electrode is wetted by the electrolyte, or that the electrode is wetted by the electrolyte and then removed from the electrolyte.
[0067] Furthermore, when the total content (wt%) of repeating units (c) and (d) in the binder resin is high, the electrolyte absorption rate is relatively high compared to the opposite case. Therefore, when the uppermost layer has a high content of repeating units (c) and (d), the electrode active material layer exhibits a high electrolyte absorption rate, thereby providing an electrode with improved resistance characteristics.
[0068] Meanwhile, copolymers A and B can be prepared using methods generally known to those skilled in the art without particular limitation. For example, repeating units selected from repeating units (a) to (d) are subjected to bulk polymerization in a reaction medium in the presence of an alginate metal salt to obtain the copolymer. The reaction medium can be a conventionally used organic solvent, specific examples of which include: aromatic hydrocarbons, such as ethylbenzene, benzene, toluene, or xylene; ketones, such as methyl ethyl ketone or acetone; aliphatic hydrocarbons, such as n-hexane; halogenated hydrocarbons, such as chloroform; alicyclic hydrocarbons, such as cyclohexane; and so on. In addition to the above components, additives such as polymerization initiators or molecular weight regulators can be used for bulk polymerization. Bulk polymerization can be carried out in a continuous processing system including, but not limited to, a feed pump, a continuous stirred vessel, a preheating vessel, an evaporation vessel, a polymer delivery pump, and an extrusion processor.
[0069] According to one embodiment of the present invention, the electrode active material layer may have a bilayer structure comprising a lower layer facing the electrode current collector and an upper layer formed on the surface of the lower layer, wherein the upper layer may comprise at least 90% by weight of a copolymer resin (B) comprising 100% by weight of a binder resin, and the lower layer may comprise at least 90% by weight of a copolymer resin (A) comprising 100% by weight of a binder resin. The electrode of the present invention is characterized by this binder resin distribution. In this way, high peel strength between the current collector and the electrode active material layer can be ensured in both dry and wet conditions, and the effect of improved ionic conductivity through high electrolyte absorption rate is provided.
[0070] Furthermore, according to one embodiment of the present invention, the content of the conductive material in the bottommost layer is equal to or higher than the content of the conductive material in the topmost layer. For example, the content of the conductive material in the bottommost layer is 1.5% by weight or more (based on 100% by weight of the bottommost layer), while the content of the conductive material in the topmost layer is 1.5% by weight or less (based on 100% by weight of the topmost layer). As described above, when the content of the conductive material in the bottommost layer is equal to or higher than the content of the conductive material in the topmost layer, even when the adhesive resin is in contact with the electrolyte, the decrease in wet adhesion relative to dry adhesion can be reduced, thus ensuring sufficient peel strength in the wet state.
[0071] Furthermore, as mentioned above, when different components exist in the upper and lower layers of the electrode active material layer, there may be mixed regions with different types of component combinations at the contact points between the upper and lower layers. This is because when the upper layer forming slurry and the lower layer forming slurry are simultaneously or at very short time intervals coated onto the current collector, and then both slurries are dried simultaneously to form the active material layer, specific mixed portions are generated at the interface where the upper layer forming slurry and the lower layer forming slurry contact before drying, and these mixed portions are formed in the form of mixed regions during the subsequent drying process.
[0072] According to one embodiment of the present invention, the electrode may be a negative electrode, a positive electrode, or both. Preferably, the electrode is a negative electrode.
[0073] When the electrode is a negative electrode, the negative electrode has a negative active material layer containing a negative active material, a conductive material, and a binder resin. Regarding the binder resin contained in the negative active material layer, reference will be made to the above description. According to one embodiment of the present invention, the electrode may further comprise at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylate, and fluororubber as the binder resin.
[0074] The negative active material may include any one selected from the following, or a mixture of two or more thereof: lithium metal oxides; carbonaceous materials such as non-graphitizable carbon, natural graphite or artificial graphite; metal composite oxides such as Li x Fe₂O₃ (0≤x≤1), Li x WO₂ (0≤x≤1), Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, a Group 1, 2 or 3 element in the Periodic Table of the Elements, halogen; 0<x≤1; 1≤y≤3; 1≤z≤8); lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides such as SnO, SnO₂, PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, Sb₂O₅, GeO, GeO₂, Bi₂O₃, Bi₂O₄ and Bi₂O₅; conductive polymers such as polyacetylene; Li-Co-Ni type materials; and titanium oxide.
[0075] According to one embodiment of the present invention, the negative current collector is not particularly limited as long as it does not cause chemical changes in the corresponding battery and has electrical conductivity. Specific examples of the negative current collector may include copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium or silver, or an aluminum-cadmium alloy, and the like.
[0076] The conductive material is not particularly limited as long as it does not cause chemical changes in the corresponding battery and has electrical conductivity. Specific examples of the conductive material include: carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal decomposition carbon black; conductive fibers, such as carbon fibers or metal fibers; metal powders, such as fluorocarbon, aluminum or nickel powders; conductive whiskers, such as zinc oxide or potassium titanate; conductive metal oxides, such as titanium oxide; conductive materials such as polyphenylene derivatives, and the like.
[0077] Meanwhile, according to one embodiment of the present invention, the electrode may be a positive electrode. The positive electrode may be obtained by the following process: mixing a positive electrode active material, a conductive material, a binder and a solvent to form a slurry, and directly coating the slurry on a metal current collector, or may be obtained by the following process: casting the slurry on a separate support, peeling off the positive electrode active material film from the support, and laminating the film on the metal current collector.
[0078] The positive electrode active material may be any active material particle selected from the group consisting of LiCoO2, LiNiO2, LiMn2O4, LiCoPO4, LiFePO4 and LiNi, or a mixture of at least two thereof 1-x-y-z Co x M1 y M2 z O2 (wherein M1 and M2 each independently represent any one selected from the group consisting of Al, Ni, Co, Fe, Mn, V, Cr, Ti, W, Ta, Mg and Mo, x, y and z each independently represent the atomic ratio of the elements forming the oxide, and 0≤x<0.5, 0≤y<0.5, 0≤z<0.5, and 0<x+y+z≤1). According to one embodiment of the present invention, the positive electrode active material may preferably include lithium cobalt oxide and / or lithium nickel cobalt manganese oxide.
[0079] The positive electrode may include at least one binder resin selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polybutyl acrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan and carboxymethyl cellulose.
[0080] Meanwhile, regarding the current collector and the conductive material contained in the positive electrode, reference will be made to the above description relating to the negative electrode.
[0081] Hereinafter, the method for manufacturing an electrode according to an embodiment of the present invention will be described. The method may include the first step to the third step as described below.
[0082] (Step 1) The steps of preparing a first layer electrode active material layer composition comprising a first layer electrode active material, a first layer electrode adhesive and a first layer electrode conductive material, and a second layer electrode active material layer composition comprising a second layer electrode active material, a second layer electrode adhesive and a second layer electrode conductive material;
[0083] (Step 2) The step of dispersing the first layer electrode active material layer composition and the second layer electrode active material layer composition obtained from (Step 1) in a dispersion medium to prepare the first layer electrode active material layer slurry and the second layer electrode active material layer slurry; and
[0084] (Step 3) Applying the first layer of electrode active material slurry and the second layer of electrode active material slurry simultaneously or sequentially onto the electrode current collector, and drying the two slurries simultaneously to form a first electrode active material layer disposed on at least one surface of the electrode current collector and a second electrode active material layer disposed on the upper part of the first electrode active material layer.
[0085] Meanwhile, according to one embodiment of the present invention, the steps of forming the first electrode active material layer and forming the second electrode active material layer can be performed simultaneously or sequentially.
[0086] In other words, the steps of forming the first electrode active material layer and the second electrode active material layer may include completely coating the first electrode active material layer slurry onto at least one surface of the electrode current collector, and coating the second electrode active material layer slurry onto the completely coated first electrode active material layer slurry, and then drying. In one variant, the steps of forming the first electrode active material layer and the second electrode active material layer may include coating the first electrode active material layer slurry onto at least one surface of the electrode current collector, and simultaneously coating the second electrode active material layer slurry onto the coated first electrode active material layer slurry, and then drying.
[0087] Specifically, a slurry to form a first electrode coating can be first coated and dried on the electrode current collector, and then a slurry to form a second electrode coating can be coated and dried on it, thereby sequentially forming a first electrode active material layer and a second electrode active material layer. Alternatively, equipment such as a dual-groove mold can be used to simultaneously coat the two slurries and then dry them to form a first electrode active material layer and a second electrode active material layer.
[0088] There are no particular limitations on the method of coating the slurry, as long as it is conventionally used in the field. For example, methods such as slot die coating, Mayer bar coating, gravure coating, dip coating, and spray coating can be used.
[0089] In another aspect of the invention, a secondary battery including the electrodes described above is provided. The secondary battery includes a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrodes, wherein at least one of the positive and negative electrodes may have the aforementioned multilayer electrode characteristics. Additionally, the secondary battery may include an electrolyte.
[0090] The diaphragm can be a conventional porous polymer membrane commonly used as a diaphragm. For example, the porous polymer membrane can be a porous polymer membrane made of polyolefin polymers (e.g., ethylene homopolymer, propylene homopolymer, ethylene-butene copolymer, ethylene / hexene copolymer, or ethylene / methacrylate copolymer). Such porous polymer membranes can be used alone or in laminated form. Alternatively, insulating films with high ion permeability and mechanical strength can be used. The diaphragm may include a safety-enhancing diaphragm (SRS) comprising a ceramic material coated to a minimum thickness on the surface of the diaphragm. Alternatively, conventional porous nonwoven webs, such as nonwoven webs made of high-melting-point glass fibers or polyethylene terephthalate fibers, can be used, but the scope of the invention is not limited thereto.
[0091] The electrolyte consists of a lithium salt as the electrolyte salt and an organic solvent used to dissolve the lithium salt.
[0092] Any lithium salt commonly used in electrolytes for secondary batteries can be used without particular limitation. For example, the anion of the lithium salt can be any one selected from the group consisting of: F - Cl - I - NO3 - N(CN)2 - BF4 - ClO4 - PF6 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - CF3CF2SO3 - (CF3SO2)2N - (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 -SCN - and (CF3CF2SO2)2N - .
[0093] The organic solvent contained in the electrolyte can be any conventionally used organic solvent without particular limitation. Typical examples of organic solvents include at least one selected from the group consisting of: propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, γ-butyrolactone, propylene sulfite, and tetrahydrofuran.
[0094] In particular, among carbonate organic solvents, ethylene carbonate and propylene carbonate, as cyclic carbonates, are organic solvents with high viscosity and high dielectric constant. Since they can readily dissociate lithium salts in the electrolyte, they are preferred for use. More preferably, when such cyclic carbonates are mixed with linear carbonates (e.g., dimethyl carbonate or diethyl carbonate) having low viscosity and low dielectric constant, electrolytes with even higher conductivity can be prepared.
[0095] Optionally, the electrolyte used according to the present invention may further include additives contained in conventional electrolytes, such as overcharge preventers.
[0096] The lithium secondary battery of embodiments of the present invention can be obtained by the following process: placing a separator between a positive electrode and a negative electrode to form an electrode assembly, introducing the electrode assembly into a bag, a cylindrical battery casing, or a prismatic battery casing, and then injecting an electrolyte therein. In one variant, the lithium secondary battery can be obtained by stacking electrode assemblies, impregnating the stack with an electrolyte, introducing the resulting product into a battery casing, and then sealing it.
[0097] According to one embodiment of the present invention, the lithium secondary battery may be a stacked, wound, stack-folded, or cable-type battery.
[0098] The lithium secondary battery of the present invention can be used as a battery cell for use as a power source in compact devices, and is preferably used as a unit cell in medium or large battery modules comprising multiple battery cells. Specific examples of medium or large devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, or energy storage systems. In particular, the lithium secondary battery can be used as a battery for hybrid electric vehicles requiring high output, as well as for new renewable energy storage batteries.
[0099] Example
[0100] Embodiments will be described more fully below to enable a readily apparent understanding of the invention. However, the following embodiments may be embodied in many different forms and should not be construed as limited to the exemplary implementations set forth herein. Rather, these exemplary implementations are provided so that the invention will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art.
[0101] Examples 1 to 6 and Comparative Examples 1 to 3: Fabrication of bilayer structured anodes with active material layers
[0102] First, graphite material, conductive material, and binder resin, serving as the negative electrode active material, were mixed with water in the proportions (wt%) shown in Tables 1 and 2 below to prepare slurries for the upper and lower negative electrode active material layers. Simultaneously, carboxymethyl cellulose (Daicel 2200) was added at a ratio of 1 part by weight, based on 100 parts by weight of the total weight of the negative electrode active material, conductive material, and binder resin. At this point, the solid content of each slurry was 49% by weight.
[0103] Using a dual-groove mold, a first layer of electrode active material slurry was coated onto one surface of a copper (Cu) foil (10 μm thick) serving as the negative electrode current collector. A second layer of electrode active material slurry was then coated onto the first layer. The slurries were then dried at 100°C for 3 minutes to form a bilayer structured electrode. The resulting upper and lower active material layers were simultaneously pressed by roll forming to obtain a negative electrode comprising a bilayer structured active material layer with upper and lower layers. The thickness ratio of the two negative electrode active material layers was approximately 1:1. The electrode active material loading in each electrode of the examples and comparative examples was 378 mg / 25 cm². 2 Furthermore, the porosity of each electrode is 31% by volume.
[0104] [Table 1]
[0105]
[0106] [Table 2]
[0107]
[0108] Meanwhile, each adhesive resin used in Tables 1 and 2 is a copolymer containing multiple repeating units, and the composition of the repeating units in the adhesive resins is shown in Tables 3 and 4 below, where the content is expressed in weight percent. The content of each repeating unit in each adhesive resin is described using... 1 The measurement is performed using 1H NMR spectroscopy. 11H NMR spectroscopy was performed using an Agilent Unity Innova 500MHz NMR instrument (Nono probe or HR MAS probe) and a Bruker Avance III HD 500MHz NMR instrument (Prodigy probe). Analytical conditions included s²pulse, rotation at 2.5 kHz, and NMR solvent (TCE-d²).
[0109] [Table 3]
[0110] Adhesive 1 49.2 38.6 4.6 2.1 5.5 Adhesive 2 42.8 38.9 6.9 3.2 8.2 Adhesive 3 55.6 38.4 2.3 1.05 2.65 Adhesive 4 41.6 38.9 7.4 3.4 8.7 BML302 36.5 39.1 9.2 4.2 11 BM451B 61.9 38.1 0 0 0
[0111] [Table 4]
[0112]
[0113] Evaluation of physical properties
[0114] Test Example 1) Measurement of Peel Strength: Evaluation of Dry Adhesion
[0115] The electrodes obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were each cut to dimensions of 15 mm x 50 mm to prepare test samples. The prepared negative electrode samples were fixed to a glass plate using substrate adhesion tape, with the active material layer of the sample facing the glass plate. Then, remover tape with dimensions of 20 mm x 50 mm was attached to the current collector of the negative electrode sample, and the peel strength was measured using a UTM system. Peel strength was measured at a peel rate of 300 mm / min and a peel distance of 50 mm at a 90° angle.
[0116] Test Example 2) Measurement of Peel Strength: Evaluation of Wet Adhesion
[0117] The electrodes obtained from Examples 1 to 6 and Comparative Examples 1 to 3 were used to manufacture batteries.
[0118] First, LiNi, as the positive electrode active material, 0.6 Co 0.2 Mn 0.2 O2, a binder (PVDF), and a conductive material (acetylene black) were introduced into NMP at a weight ratio of 96.5:1.5:2 to prepare a slurry (70% by weight solids) for forming the positive electrode active material layer. The slurry was coated onto an aluminum foil (thickness: approximately 10 μm) and dried at 130 °C for 2 minutes to prepare the positive electrode.
[0119] A porous membrane (10 μm) made of polyethylene was prepared as a separator. Then, the positive electrode, separator and negative electrode were stacked in sequence, and the resulting stack was subjected to a lamination process of pressurizing the stack at 80 °C to obtain the electrode assembly.
[0120] The electrode assembly was introduced into a pouch cell housing, and an electrolyte was injected into it to obtain a battery. An electrolyte was prepared by mixing ethylene carbonate, propylene carbonate, ethyl propionate, and propyl propionate in a weight ratio of 2:1:2.5:4.5 and introducing 1.2 M LiPF6.
[0121] The batteries of both the examples and comparative examples were charged to 4.25V in constant current (CC) mode at 1.0C, charged to a cutoff current of 0.005C in constant voltage (CV) mode, and then discharged to 3V in constant current mode at 1C. The charge / discharge cycle was repeated 100 times. The test was conducted at room temperature (25°C). Then, each battery was disassembled to remove the negative electrode, and the adhesion force of the negative electrode was measured in the same manner as in Test Example 1).
[0122] Test Results
[0123] The results of dry and wet adhesion of the negative electrode active material layers in Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 5 below. The results show that the negative electrodes of Examples 1 to 6 exhibit excellent dry adhesion, and in particular, show a small decrease in wet adhesion relative to dry adhesion, thus ensuring a high level of adhesion even in a wet state. In Table 5, adhesion retention rate is the percentage of wet adhesion based on dry adhesion.
[0124] [Table 5]
[0125]
[0126] Example 6 and Comparative Example 1 used the same amount of conductive material in both the upper and lower layers, but the contents of repeating units (c) and (d) differed. When Example 6 was compared with Comparative Example 1, Example 6 showed a higher adhesion retention rate compared to Comparative Example 1. In the case of Comparative Example 2, even though the content of conductive material in the lower layer was higher, the contents of repeating units (c) and (d) in the lower layer were also higher than those in the upper layer. As a result, Comparative Example 2 showed a lower adhesion retention rate compared to the Example 1. In the case of Comparative Example 3, the contents of repeating units (c) and (d) in the lower layer were higher than those in the upper layer, and the content of conductive material in the lower layer was lower. As a result, Comparative Example 3 showed a significantly lower adhesion retention rate.
Claims
1. An electrode for an electrochemical device, comprising: Electrode current collector; And a multilayer structured electrode active material layer, wherein the multilayer structured electrode active material layer is disposed on at least one surface of the electrode current collector and has two or more stacked sublayers. The electrode active material layer comprises an electrode active material, a binder resin, and a conductive material. The bottom layer of the multilayer structured electrode active material layer includes copolymer resin A as a binder resin, and the top layer is disposed above the bottom layer. Furthermore, the top layer of the multilayer structured electrode active material layer includes copolymer resin B as a binder resin. The copolymer resin A is a copolymer containing at least one repeating unit selected from vinyl aromatic monomer a; conjugated dienyl monomer b; repeating unit c derived from vinyl cyanide compound; and repeating unit d derived from (meth)acrylate compound. The copolymer resin B is a copolymer containing a vinyl aromatic monomer a; a conjugated diene monomer b; a repeating unit c derived from a vinyl cyanide compound; and a repeating unit d derived from a (meth)acrylate compound. The sum of the weight percentages of repeating unit c and repeating unit d in the adhesive resin of the uppermost layer is greater than the sum of the weight percentages of repeating unit c and repeating unit d in the adhesive resin of the lowermost layer. The total content of repeating unit c and repeating unit d in the adhesive resin of the lowest layer is less than 20% by weight.
2. The electrode for the electrochemical device according to claim 1, wherein, The vinyl cyanide compound is at least one selected from acrylonitrile and methacrylonitrile.
3. The electrode for the electrochemical device according to claim 1, wherein, The (meth)acrylate compound is selected from at least one of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, and 2-ethylhexyl methacrylate.
4. The electrode for the electrochemical device according to claim 1, wherein, The bottommost layer includes copolymer resin A as an adhesive resin, wherein copolymer resin A contains at least two selected from vinyl aromatic monomer a, conjugated diene monomer b, repeating unit c derived from vinyl cyanide compound and repeating unit d derived from (meth)acrylate compound.
5. The electrode for the electrochemical device according to claim 1, wherein, The bottommost layer comprises a quaternary copolymer of styrene-butadiene-acrylonitrile-repeating unit d and / or a binary copolymer of styrene-butadiene as an adhesive resin, and the repeating unit d is derived from butyl acrylate and / or methyl methacrylate.
6. The electrode for the electrochemical device according to claim 1, wherein, The bottom layer comprises a quaternary copolymer of styrene-butadiene-acrylonitrile-repeating unit d as an adhesive resin, and the repeating unit d is derived from butyl acrylate and / or methyl methacrylate.
7. The electrode for the electrochemical device according to claim 1, wherein, The bottommost layer of conductive material accounts for 100% by weight, and the content of the bottommost layer by weight is equal to or higher than the content of the topmost layer by weight, which accounts for 100% by weight.
8. The electrode for the electrochemical device according to claim 1, wherein it is a negative electrode.
9. A lithium-ion secondary battery comprising the electrode for the electrochemical device as described in claim 1.
Citation Information
Patent Citations
Can opener of the ups and downs
KR1020200145516A
Anode for secondary battery, manufacturing method therefor, and secondary battery comprising same
CN107925058A
Binder with improved adhesive strength and coatingproperties for secondary battery
KR1020070023141A